2008
DOI: 10.1002/ange.200703580
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Aromatic Amination Mediated by a Diiron Complex

Abstract: Auf halbem Wege unterbrochen: Ein effizienter Amintransfer auf einen biomimetischen Dieisenkomplex verläuft unter Insertion von einer oder zwei Tosylamingruppen in einen Benzylsubstituenten des Liganden (siehe Struktur). Das Monoinsertionsprodukt wurde röntgenkristallographisch und durch weitere physikalische Methoden als Tosylanilinato‐Dieisen(III)‐Komplex charakterisiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…We have reported that the diiron(III,II) complex 1 (Scheme ) was very efficient in catalytic nitrene transfers to alkenes and thioanisole 12. In addition, its unprotected analogue (with hydrogen atoms in place of chlorine on the ortho benzylic positions) was shown to mediate fast and quantitative ortho ‐amination of the dangling benzyl group of the ligand 13. The remarkable reactivity of these systems prompted us to investigate the nature of the species active in the nitrene transfer to gain information useful to design efficient Fe catalysts for these reactions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported that the diiron(III,II) complex 1 (Scheme ) was very efficient in catalytic nitrene transfers to alkenes and thioanisole 12. In addition, its unprotected analogue (with hydrogen atoms in place of chlorine on the ortho benzylic positions) was shown to mediate fast and quantitative ortho ‐amination of the dangling benzyl group of the ligand 13. The remarkable reactivity of these systems prompted us to investigate the nature of the species active in the nitrene transfer to gain information useful to design efficient Fe catalysts for these reactions.…”
Section: Methodsmentioning
confidence: 99%
“…Then both bridging and terminal binding modes of the N(H)Ts group were considered. Moreover, because in 1 the solvent binds in the position trans to the bridging phenoxide21, 22 whereas in the insertion product of the non‐chloroprotected ligand, the N‐benzyltosylate is bound in the cis position,13 we considered both cis and trans isomers for the calculations of 3 and 4 . First, we explored the tosylamido complex {Fe III Fe III ‐NHTs} 4 and observed that the terminal mode is clearly preferred, the bridging structure being about 23 kcal mol −1 higher.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence suggesting the involvement of a σ-complex was obtained from isotope labeling experiments. Similarly, a diiron complex was also found to be amenable to aromatic C-H amination when treated with tosyliminoiodane (Scheme 5) [49]. Interestingly, although the dinuclear complex showed a weak ability to mediate oxygen transfer, it was very efficient in promoting nitrene transfer reactions, and even gave significant formation of double aromatic C-H amination products.…”
Section: C-h Amination With Non-heme-type Ironimido Speciesmentioning
confidence: 99%